Sex Differences in Risk Factors for Transient Ischemic Attack in a Chinese Population - Wang, Wendi; Sun, Pei; Han, Fengyue; Qu, Chuanqiang (Frontiers in Neurology, 2021)
Introduction: This study aimed to collect and evaluate basic information of a stroke screening population in eastern China and to compare distribution differences in risk factors between males and females in a transient ischemic attack (TIA) population. Methods: A standardization of the risk factors for stroke was performed according to an implementation plan of stroke in a high-risk population screening and intervention project in Shandong Province. Of the 231,289 residents, 8,603 patients with a previous TIA were identified and risk factors in this cohort were analyzed for sex differences. Results: In our initial cohort of 231,289 residents, we found 3,390 men and 5,213 women with TIA, accounting for a prevalence of 3.1% and 4.2%, respectively. Risk factors for TIA were hypertension, atrial fibrillation, diabetes, smoking, lack of exercise, overweight, and family history of stroke. In our TIA cohort, we found that the prevalence of smoking was significantly higher in men (41.3%) compared with that found in women (4.2%). Further, hypertension (58.8% vs. 55.5%) and family history of stroke (22.3% vs. 20.0%) were more prevalent in men compared with women, whereas atrial fibrillation (14.7% vs. 16.4%), diabetes (11.1% vs. 13.2%), lack of exercise (27.2% vs. 28.0%), and overweight (29.5% vs. 35.7%) were less prevalent. Conclusions: In our TIA cohort from eastern China, we found significant sex differences for the risk factors of hypertension, atrial fibrillation, smoking, diabetes, and overweight.